Design of PV fed single-switch transformer less topology powered electric vehicle (2024)
As a result of an increase in the availability of resources that were not harmful to the environment, solar energy applications shot to popularity. Photovoltaic cells power systems that necessitate DC-DC converters because of their low voltage output. This investigation uses photovoltaic cells (PV) to power a high-voltage gain design with just one switch and no transformer. The proposed circuit utilizes a single regulated switch, which contributes to a reduction in switching losses. It requires fundamental pulse regulation. The network used a switched capacitor cell and an LC passive filter to provide an accurate step-up voltage. We can obtain the equation for the step-up voltage gain from the steady-state continuous conduction mode. The equations used for the theoretical design of converters include energy. To show that the topology is comparable with other modern converters that have been published, a comparison was made between it and other converters. In order to validate the converter's effectiveness, simulations built in MATLAB and Simulink are used.